PEMBELAJARAN SENI TARI DI SMA NEGERI 1 LENGAYANG KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Putri, Noriza; Ayuthia Mayang Sari (Universitas Negeri Padang, 2026)
Abstract This study aims to understand and describe the process of implementing dance art learning at SMA Negeri 1 Lengayang, Lengayang District, Pesisir Selatan Regency. This type of research is qualitative research with a descriptive method. The research instrument is the researcher themselves, assisted with writing tools and a camera. Data is collected through literature review, observation, interviews and documentation. The steps in analysing the data are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of dance art learning at SMA Negeri 1 Lengayang, Lengayang District, Pesisir Selatan Regency has three stages, namely planning, implementation, and evaluation. In the planning stage, the teacher structures learning by referring to the Merdeka Curriculum teaching module which contains learning outcomes, learning objectives, learning objectives, learning objective sequences, methods, media, and assessments. At the implementation stage, learning was conducted over four meetings held gradually, with the first meeting discussing the meaning and symbols of dance, the second meeting discussing the function of the meaning and symbols of dance, the third meeting discussing the meaning and symbols in dance makeup and costumes, and the fourth meeting discussing the meaning and symbols in levels and floor patterns. In its implementation, the learning activities went through the preliminary, main, and closing stages, but the teacher still tended to use a lecture method combined with question-and-answer sessions and utilising simple media such as textbooks and blackboards, resulting in low student involvement and activity and a teacher-centred approach to learning. At the evaluation stage, assessment emphasises more on formative assessment carried out continuously through observations of student participation, discussions, and presentations, as well as providing direct feedback to understand their grasp of the material, whereas summative assessment is not specifically conducted in the form of final tests.